A methods engineering study on Lovely Dianne Brassiere - Ilagan, Gazel (College of Engineering, 1999)
This study is a compilation of basic information and analysis on the company of which the group has taken interest in . This company is known as Lovely Dianne Brassiere (LDB), a garments business in San Rafael, Bulacan. LDB produces undergarments, namely : brassieres, men's underwear, ladies' sandoes and pantylets with the first two mentioned products as their main products. Their production is determined by demand which ranges from 100 to 200 dozen units a week (on brassieres alone). LDB is a considerably small company with a workforce of only 25 sewers and cutters handling 19-25 machines. Their market includes nearby fiesta towns, some provinces from Aparri to the Visayas region. From the problem analysis, the group found out that these areas needed attention : (1) the flow of materials; (2) the assembly line and delay of operations; and the (3) unavailability of materials. The root causes found by the group that brought the aforementioned effects were the (1) lack of sewers for some operations and the presence of idle time for some operations ; (2) the inefficient plant layout and the lack of temporary storage facilities; and the (3) lack of communication of managers and workers and the lack of a forms and records systems. The group, after generating several alternatives for each problem, recommended a particular layout to solve the problem of obtaining a better flow of materials. The group also recommended a way to reduce idle time for some operations and eliminate as much as possible the lack of sewers for some operations by suggesting an output value per week and operation time per day (this was determined through the steps in balancing the assembly line). As a result, this can increase efficiency. The group also made recommendations on the Systems and Procedures by establishing forms and records that would serve as databanks for the company to maximise control. The ways of implementing these recommendations have also been devised.